(untitled) - Kehal, H. S. (New York, 2004)
This volume examines foreign investment in developing countries both from a theoretical perspective and country specific perspective. It covers strategies to maximize the benefits that draw from the inward investment flow as well as examining foreign investment as a vehicle for international economic integration. The book focuses on foreign investment in the third and fourth largest economies of the world--the Peoples Republic of China and India--in addition to Indonesia, Malaysia and other countries.
Keywords: Investments, foreign